2020
DOI: 10.1155/2020/2317929
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study Evaluating the Stages of Change in Food Consumption with Warning Labels among Chilean University Students

Abstract: Objective. To analyze the stage of change in food consumption with warning labels among Chilean university students. Materials and Methods. Cross-sectional study which applied surveys in universities from all over the country. Study included 4807 participants of 18 to 40 years of both sexes who were asked about the level of knowledge of the new food law and food consumption with warning signals, including questions regarding their willingness to behavior change according to Prochaska’s transtheoretical model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…A study that confirms the aforementioned found that despite university student knowing the importance of warning labels on food consumption, they showed strong pre-contemplative stages and resistance before changing their consumption habits [ 29 ]. These results clearly show the high degree of rooted eating habits in this population, but in particular, in people with overweightness or obesity [ 30 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A study that confirms the aforementioned found that despite university student knowing the importance of warning labels on food consumption, they showed strong pre-contemplative stages and resistance before changing their consumption habits [ 29 ]. These results clearly show the high degree of rooted eating habits in this population, but in particular, in people with overweightness or obesity [ 30 ].…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it is recommendable that critical periods should be taken into account in the public health system as a potential hazard to populations health, because the sum of short critical periods during a year could affect people’s health in the future. Thus, two points are important to highlight: The first is that intervention in overweight/obese university students focusing on acquiring positive eating habits and lifestyles should be prioritized [ 29 , 34 , 42 ]. The second is that the current way to face a critical period by the Chilean public health system neither guarantees nor promotes modification on eating and physical activity behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies evaluated the consumers' behaviour change stage during the first phase of the CFL implementation (Agúero et al. , 2020a, b).…”
Section: Resultsmentioning
confidence: 99%
“…Females consumed more fruits and vegetables and followed a vegetarian pattern more often than male students. Female students were more concerned about a healthy diet and read food labels more often than male students [ 17 , 41 ]. Males preferred a convenience pattern [ 15 ], meat [ 15 , 16 ] and processed meat [ 40 ], and take-away and fast foods [ 16 , 40 ] more often than females.…”
Section: Discussionmentioning
confidence: 99%